THE RELATIONSHIP BETWEEN THE USE OF 3-MONTH INJECTABLE CONTRACEPTIVES (PROGESTINS) WITH WEIGHT GAINING IN FAMILY PLANNING ACCEPTORS IN SIALAMBUE VILLAGE, PADANG LAWAS REGENCY IN 2020: THE RELATIONSHIP BETWEEN THE USE OF 3-MONTH INJECTABLE CONTRACEPTIVES (PROGESTINS) WITH WEIGHT GAINING IN FAMILY PLANNING ACCEPTORS IN SIALAMBUE VILLAGE, PADANG LAWAS REGENCY IN 2020 - Mkes, Henny Sahriani (Jurnal Kesehatan Ilmiah Aufa Royhan, 2021)
Most family planning acceptors in Indonesia are dominated by injection family planning acceptors at 63.7%. One of the side effects of 3-month injectable contraception is weight gain, women who use 3-month injectable contraception have an average weight gain of 11 pounds or 5.5 kg and experience an increase in body fat of 3.4% within 3 years of use. . The purpose of the study was to determine the relationship between the use of 3-month injectable contraceptives (progestin) with weight gain in family planning acceptors in Sialambue village, Padang Lawas district in 2020. This study was a quantitative study with a cross sectional approach. The population is all acceptors of 3-month injection KB in Sialambue village, Padang Lawas Regency in 2021, totaling 45 people. The sampling technique is purposive sampling and the sample is 45 people. The results showed that there was a significant relationship between the use of 3-month injectable contraceptives (progestin) and weight gain in family planning acceptors with p = 0.013 < = 0.05. It is recommended for mothers who want to become family planning acceptors to be wiser in determining the type of contraception to be used. Pay attention to the benefits, advantages and side effects of contraception to be used.